Values of Character Education According to KH. Hasyim Asy'ari and Its Relevance - Mohammad Saat Ibnu Waqfin (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The history of the industrial revolution itself goes through various stages, starting with industrial revolution 1.0, 2.0, 3.0, to industry 4.0. The industrial phase is a real change from existing changes. Industry 1.0 is characterized by mechanization of production to support the effectiveness and efficiency of human activities, industry 2.0 is characterized by mass production and quality standardization, industry 3.0 is characterized by mass customization and flexibility in automation and robot-based manufacturing. Industry 4.0 is here to replace industry 3.0 which is characterized by physical cyber and manufacturing collaboration. The term industry 4.0 originates from a project initiated by the German government to promote the computerization of manufacturing. As science and technology advances, it is not impossible that education and all its systems will also experience changes. For example, in the learning process which was previously carried out face to face, with the industrial revolution 4.0, learning can be carried out online, such as using social media or other supporting media. The challenge of Indonesian education itself is how education can be more innovative and creative by utilizing existing technological developments, education that has characteristic values. Heckeu et al added that the challenges of the industrial revolution 4.0 also provide changes to the social system in education and society. First, changes in demographics and social values. Second, the growth of process complexity which includes; technical skills, process understanding, learning motivation, tolerance, decision making, problem solving and analytical skills